DESIGN DEVELOPMENT AND TECHNICAL ANALYSIS OF AUTO CHECKING HARDNESS MACHINE - A STUDY CASE OF HARDNESS TESTER HR-522 SERIES - Caesar, Bernardus Plasenta Previo; Dzulfikar, Muhammad Faiz; Prabowo, Aditya Rio; Pratama, Pandu Sandi; Cho, Joung Hyung (Journal of Applied Engineering Science, 2021)
A hardness-checking machine is a crucial tool in engineering study, especially in the mechanical and manufacturing process. It usually used to measure, calibrate, and standardize the quality of the product. It is based on the field problem in Akebono Brake Astra Indonesia for using more manual tools to achieve product demands. It is considering those issues, the development of a modified hardness checking tool from manual operation to automatic operation. Using automatic operation is useful in time and savings for other manual tools. The automatic tool applies the 3-axes system mechanism using Festo linear actuator with the servo motor. The testing capacity of automatic devices is equal to more manual devices. The frame of the auto-checking hardness machine is assessed by applying load variations. From the other similar work of auto checking hardness machine, this paper provides the comparison of various aluminum frame types based on different tensile strength and cross-sectional area values. The other analysis is calculating the base plate for hardness testing. There are 9 points of testing to calculate the use of linear guides for the base plate. The results are the excellent value of tensile strength has good results of displacement and maximum stress.